KEBIJAKAN PEMERINTAH DALAM UPAYA PENCEGAHAN DAN PEMBERANTASAN MAFIA TANAH - Ruslina Dwi Wahyuni; Irmayani Misrah (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
The land mafia is an extraordinary crime that is now increasingly rampant, so serious action is needed from the government and related stakeholders as well as the community in efforts to prevent and eradicate it. This paper discusses the policies carried out by the government and innovations in efforts to prevent the rise of the land mafia. This paper discusses the policies carried out by the government and innovations in efforts to prevent the rise of the land mafia. Methods used using empirical juridical legal research methods. This paper concludes that the government has made a policy in tackling land mafia, as well as innovating land services as a preventive measure. It requires collaboration from all parties as well as integrity from legal actors as well as public awareness and concern.